2021
DOI: 10.1155/2021/2619327
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Brainstem Anesthesia after Retrobulbar Block for Globe Rupture Repair

Abstract: Purpose. To present a rare case of brainstem anesthesia from retrobulbar block and discuss evidence-based methods for reducing the incidence of this complication. Case. A 72-year-old female, was given a retrobulbar block of 5 mL of bupivacaine 0.5% for postoperative pain management, after a globe rupture repair under general anesthesia. Prior to injection, the patient was breathing spontaneously via the anesthesia machine circuit and had not received any additional narcotics/muscle relaxants for 2.5 hr (with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This type of anesthesia includes different sub-types, such as topical anesthesia [13][14][15] , subconjunctival anesthesia [16][17][18] , retrobulbar anesthesia, peribulbar anesthesia, sub-Tenon's anesthesia [9,[19][20] , medial canthus epiescleral anesthesia [21] and facial nerve block. Topical anesthesia has become a common form of anesthesia; however, it requires that the surgery is performed quickly and efficiently to minimize stress on the patients [22] , patient cooperation [23] , experienced surgeon [10] and it doesn't provide the same level of pain relief as peribulbar anesteshia [24][25] . We still prefer loco-regional anesthesia not only for posterior segment or glaucoma surgery but also because it is the preferred method for anterior segment surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of anesthesia includes different sub-types, such as topical anesthesia [13][14][15] , subconjunctival anesthesia [16][17][18] , retrobulbar anesthesia, peribulbar anesthesia, sub-Tenon's anesthesia [9,[19][20] , medial canthus epiescleral anesthesia [21] and facial nerve block. Topical anesthesia has become a common form of anesthesia; however, it requires that the surgery is performed quickly and efficiently to minimize stress on the patients [22] , patient cooperation [23] , experienced surgeon [10] and it doesn't provide the same level of pain relief as peribulbar anesteshia [24][25] . We still prefer loco-regional anesthesia not only for posterior segment or glaucoma surgery but also because it is the preferred method for anterior segment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the necessity for general anesthesia in ocular surgery, blockage of the optic nerve using needle-based blocks is widely implemented to achieve akinesia and analgesia. Complications of the procedure (e.g., haemorrhage [4] , iatrogenic injection of the local anaesthetic into the opticnerve sheath [5] , penetration of the ocular glove [6] , amaurosis [7] , iatrogenic ophthalmic artery occlusion [8][9] or brainstem anaesthesia [10] ) are rare. Although these complications may be avoided with topical administration, loco-regional anesthesia is preferred in procedures requiring both akinesia and deep anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The second mechanism is a systemic absorption of the anesthetic product (venous/arterial). The third mechanism, the most commonly accepted and the one incriminated in our case, is the puncture of the dura mater which leads to a diffusion of the anesthetic product in the subarachnoid space, and consequently an accumulation of the product in the meninges [1], [2]. Studies on cadavers have confirmed this hypothesis of dye reaching the brainstem after intra-orbital subdural space puncture [2], [3].…”
Section: Discussionmentioning
confidence: 61%
“…The third mechanism, the most commonly accepted and the one incriminated in our case, is the puncture of the dura mater which leads to a diffusion of the anesthetic product in the subarachnoid space, and consequently an accumulation of the product in the meninges [1], [2]. Studies on cadavers have confirmed this hypothesis of dye reaching the brainstem after intra-orbital subdural space puncture [2], [3]. The latter is characterized by a latency between the injection of the product and the appearance of the signs because of the time necessary for the product to arrive at the level of the brainstem [2].…”
Section: Discussionmentioning
confidence: 89%
“…1 Although the retrobulbar approach has a higher success rate, it is associated with a higher risk of complications when compared to peribulbar blocks, 2 such as brainstem anesthesia. 3 The administration of short-acting local anesthetics can cause rapid-onset and short-duration neurological changes, with full recovery after the block subsides.…”
mentioning
confidence: 99%